A new landscape of host–protozoa interactions involving the extracellular vesicles world. Issue 12 (10th July 2018) - Gavinho, Bruno; Rossi, Izadora Volpato; Evans-Osses, Ingrid; Inal, Jameel; Ramirez, Marcel I.
Abstract: Extracellular vesicles (EVs) are released by a wide number of cells including blood cells, immune system cells, tumour cells, adult and embryonic stem cells. EVs are a heterogeneous group of vesicles ( 30–1000 nm) including microvesicles and exosomes. The physiological release of EVs represents a normal state of the cell, raising a metabolic equilibrium between catabolic and anabolic processes. Moreover, when the cells are submitted to stress with different inducers or in pathological situations (malignancies, chronic diseases, infectious diseases.), they respond with an intense and dynamic release of EVs. The EVs released from stimulated cells vs those that are released constitutively may themselves differ, both physically and in their cargo. EVs contain protein, lipids, nucleic acids and biomolecules that can alter cell phenotypes or modulate neighbouring cells. In this review, we have summarized findings involving EVs in certain protozoan diseases. We have commented on strategies to study the communicative roles of EVs during host–pathogen interaction and hypothesized on the use of EVs for diagnostic, preventative and therapeutic purposes in infectious diseases. This kind of communication could modulate the innate immune system and reformulate concepts in parasitism. Moreover, the information provided within EVs could produce alternatives in translational medicine.